Contextualizing the nature of trauma in the juvenile justice trajectories of girls. Issue 2 (3rd April 2019) - Anderson, Valerie R.; Walerych, Brinn M.
Abstract: The proportion of girls involved in the juvenile justice system has steadily increased over the last few decades. Previous research has indicated that the presence of girls in the juvenile justice system is often linked to trauma and violence, and the subsequent criminalization of behaviors associated with traumatic experiences. The present study examined qualitative interview data from juvenile court officers ( n =  24) in a mid-sized juvenile county court to review the types and extent of trauma experienced by girls and the connection of trauma to juvenile justice trajectories. A secondary goal of the study was to determine the current level of access to trauma-informed care for female youth and how equipped juvenile court are to manage and provide trauma-related services. Results indicated that girls experience high rates of family violence, neglect, emotional trauma, and sexual abuse. Juvenile court officers described how these events were often connected to their pathways into the justice system; however, there was less discussion of trauma-specific care for girls. These perceptions and explanations of traumatic events directly shape prevention, intervention, and policy responses by the justice system. This study raises concerns related to how researchers and practitioners can shift the focus from trauma as an individual-level deficit to an ecological understanding of trauma and the integration of trauma-informed practice in juvenile justice contexts.